Antiviral Adaptor MAVS Promotes Murine Lupus With a B Cell Autonomous Role - Sun, Wenxiang; Wang, Hongsheng; Qi, Chen-Feng; Wu, Juan; Scott, Bethany; Bolland, Silvia (Frontiers in Immunology, 2019)
Systemic lupus erythematosus (SLE) is an autoimmune disorder characterized by increased production of autoantibodies, which commonly target nuclear antigens, and concomitant deposition of immune complexes that cause inflammation in tissues. SLE is often associated with increased systemic expression of type I interferons, in some cases due to dysregulation in nucleic acid-sensing innate pathways. There is strong genetic evidence for a link between cytoplasmic RNA sensing pathways (RIG-I/MDA5) and SLE, both in human patients and murine models, however questions still remain regarding pathway initiation, cell types involved and downstream effects. Here we show that MAVS, an essential adaptor for RIG-I/MDA5 signaling, is necessary for all symptoms of autoimmune disease that develop spontaneously in the lupus model FcγRIIB-/- mice. This effect was independent of type I interferon signaling, TLR7 expression or STING, all three factors that have been connected to autoimmunity. Mixed bone marrow reconstitution experiments showed reduced occurrence in autoimmune germinal centers and diminished autoantibody production by MAVS-deficient B cells. Thus, MAVS plays a B cell intrinsic role in autoreactive B cell activation that is independent of its anti-viral functions and independent of elevated type I interferon expression.